Six Air Pollutants Associated With Increased Risk of Thyroid Nodules: A Study of 4.9 Million Chinese Adults - Zhang, Yunjing; Wang, Kai; Qin, Wei; Jin, Cheng; Song, Yiqing; Jia, Peng; Wang, Shengfeng; Song, Yongfeng; Ning, Yi; Li, Liming (Frontiers in Endocrinology, 2021)
ABSTRACT Background: Thyroid nodules has become a significant public health issue worldwide with a rapidly increasing prevalence. However, its association with outdoor air pollution remains poorly understood. We aim to investigate the relationship between six outdoor air pollutants (PM2.5, PM10, NO2, SO2, CO, and O3) and risk of thyroid nodules. Methods: We utilized a database including 4,920,536 participants who attended annual physical examinations in Meinian HealthCare Screening Center in 157 Chinese cities in 2017. City-specific concentrations of six pollutants (PM2.5, PM10, NO2, SO2, CO, and O3) from 2015 to 2017 were estimated based on China’s National Urban Air Quality Real Time Publishing Platform. Thyroid nodule was measured with ultrasound. Multivariable Logistic regression was used to examine the associations between air pollutants and thyroid nodules with adjustment for age, sex, education, smoking, body mass index, fasting blood glucose, triglyceride, low density lipoprotein cholesterol, high density lipoprotein cholesterol, urine iodine, gross domestic product, and thyroid stimulating hormone. We conducted stratified analyses to investigate potential effect modification by sex, age, and urine iodine groups. Results: Approximately 38% of participants (1,869,742) were diagnosed with thyroid nodules. Each of the six air pollutants was significantly and linearly associated with the risk for thyroid nodules. The adjusted odds ratios [95% CI] for every increase of 10 μg/m3 for PM2.5, PM10, NO2, SO2 and O3 were 1.062 [1.061, 1.064], 1.04 [1.03, 1.04], 1.10 [1.09, 1.10], 1.11 [1.11, 1.12] and 1.151 [1.149, 1.154], respectively; The odds ratio for each increase of 1 mg/m3 for CO was 1.50 [1.49 to 1.52]. Furthermore, these associations were significantly higher in the participants who were men, younger, or having lower urine iodine level (p<0.001). Conclusion: Six air pollutants may contribute to high prevalence of thyroid nodules in China.